Successful treatment of Serratia Marcescens peritonitis in a patient receiving peritoneal dialysis. Issue 2 (11th December 2020) - Yang, Ning; Li, Longkai
Abstract: An old man receiving peritoneal dialysis was diagnosed with Serratia marcescens peritonitis, a rare case with poor prognosis. Powerful antibiotics based on culture results and enough duration cured the case successfully despite its high virulence. Abstract : An old man receiving peritoneal dialysis was diagnosed with Serratia marcescens peritonitis, a rare case with poor prognosis. Powerful antibiotics based on culture results and enough duration cured the case successfully despite its high virulence.